Luxury Transportation Innovations for Sustainability: Implementing of Research & Development - Rahmawati, Ema; Sugiarto, Sugiarto; Hendratono, Tonny; Are, Robert La; Bahri, Asep Syaiful (Pelopor Publikasi Akademika, 2025)
This research focuses on the use of Artificial Intelligence (AI) and Virtual Reality (VR) in luxury tourism buses, specifically the Omah Sultan Juragan 99 Trans in Malang, East Java, Indonesia. The research and development (R&D) approach, supported by qualitative and quantitative data, aims to evaluate the effectiveness of AI and VR in enhancing the tourist experience. Through in-depth observations, interviews with key informants, and field trials, the study investigates various elements, such as smart technology, VR services, AI as a virtual guide, and the overall user experience. The findings show that the integration of AI and VR enhances the travel experience by providing personalized virtual tours, improving the service quality, and contributing to the sustainability of the luxury bus service. The study results suggest that AI and VR can play a pivotal role in modernizing tourism transportation by offering innovative, immersive, and interactive tourist experiences. The innovation of AI and VR in this context is a groundbreaking contribution to the tourism sector, addressing the emerging demand for personalized, high-tech travel services in luxury transportation. Future research can further explore the scalability of these technologies across different regions and tourism sectors to validate their broader applicability.